Exploring forced marriage in Islam: Analysis of Imam Al-Shafi'i's perspective, Indonesian Islamic marriage law, and human rights considerations - Asnita, Dessy (Jurnal Anifa: Studi Gender dan Anak, 2024)
The Wali mujbīr is a guardian who has the right to marry off his daughters without their prior consent. Although Imam Al-Syāfi'ī supports this concept, the Marriage Law Number 1 of 1974 and the Compilation of Islamic Law do not explicitly recognize the ijbār right. This article examines the existence and implications of the mujbīr guardian's right in the context of Islamic law in Indonesia, considering the voluntary principle in marriage. This research utilizes a qualitative approach with primary data from the Al Umm book and Indonesia's Compilation of Marriage Laws. The results indicate that the ijbār right is not contradictory to Islamic law in Indonesia and does not violate Human Rights, although the guardian must meet certain conditions before forcing a marriage. This highlights the debate surrounding decisions made on the assumption that daughters are incapable of making their own decisions in marriage.